Iz starega Rima prek Haaga in Visbyja do Rotterdama - Jerman, Boris (Podjetje in delo, 2024)
The article discusses the liability of the maritime carrier. Until the end of the 19th century, its liability was strict, as it developed in the period of ancient Rome based on the praetorian edict. The change in the liability of the maritime carrier from strict to fault liability is related with strong position of carriers in the 19th century, when, based on contractual freedom, they were able to place provisions on exemption from liability in the bills of lading, so that they were not responsible for almost any damage. Such a situation required the intervention of the legislator. The carrier was given the obligation to prepare the ship for sailing with due diligence, thus becoming liable for faults. It could not get rid of this obligation, it could only relieve itself of its responsibility in specific cases determined by the legislator.